2019
DOI: 10.1007/s00038-019-01210-7
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of smartphones on physical activity promotion? A systematic review and meta-analysis

Abstract: Objectives To identify and evaluate the effect of interventions that used cell phones as a means to promote physical activity (PA). Methods The databases searched were MedLine/PubMed, Scopus, SPORTDiscus, PsycINFO, Science Direct, Lilacs, and SciELO. After removing duplicates, applying exclusion criteria, and checking the reference lists, 45 studies were reviewed. The Downs and Black (D&B) scale measured methodological quality, and a random effect model was used to compute the meta-analysis of PA by the report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 73 publications
1
48
0
Order By: Relevance
“…Importantly, building physical activity into the day, using approaches such as active travel 37 or by incorporating multiple small amounts activity throughout the day can provide tangible benefits 38 . Pedometer-supported behaviour change approaches which incorporate setting of progressive physical activity goals, and provide selfmonitoring and feedback of activity levels are effective at increasing physical activity levels 39 , and there is emerging evidence that smartphone-based approaches can be effective for promoting physical activity 40 . However, it is important that targets are personalised and realistic -for example, for someone who is very inactive, initially increasing step count by 1000 per day, equivalent to about 10 extra minutes of walking, can potentially provide benefit and provides a platform for further increases in activity with time.…”
Section: Communicating Advicementioning
confidence: 99%
“…Importantly, building physical activity into the day, using approaches such as active travel 37 or by incorporating multiple small amounts activity throughout the day can provide tangible benefits 38 . Pedometer-supported behaviour change approaches which incorporate setting of progressive physical activity goals, and provide selfmonitoring and feedback of activity levels are effective at increasing physical activity levels 39 , and there is emerging evidence that smartphone-based approaches can be effective for promoting physical activity 40 . However, it is important that targets are personalised and realistic -for example, for someone who is very inactive, initially increasing step count by 1000 per day, equivalent to about 10 extra minutes of walking, can potentially provide benefit and provides a platform for further increases in activity with time.…”
Section: Communicating Advicementioning
confidence: 99%
“…A 2016 systematic review [18] and a 2019 meta-analysis [20] of studies using apps to improve PA found that few stand-alone app interventions reported positive effects. Another recent meta-analysis [21] and systematic review [19] on the other hand found that app-based interventions increased PA. The still limited number of RCTs in this area (n < 10), due in part to the rapid pace of app development and rollout, may help explain the discrepancies [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance our understanding of this rapidly evolving field non-RCT alternatives (e.g., quasi-experimental designs) are needed [19,22,23]. Longitudinal designs in particular are warranted given the majority of studies do not exceed three months [19][20][21] even though sustained PA is needed to attain many of the purported health benefits [1]. Rigorous quasi-experimental evaluations of top tier commercial apps (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The number of mHealth app downloads also increased by 16% from 2016 to 2017 (3.2 to 3.7 billion) [ 7 ]. Although both supply (apps published in stores) and demand (app downloads) is growing, low engagement (with engagement measured as repeated usage, consistent with behavioral science approaches [ 8 , 9 ]) has resulted in small effect sizes and presented hurdles for financial sustainability continues to be a challenge for the industry [ 10 - 13 ]. For instance, 90% of all mHealth apps are uninstalled within 30 days, and 83% of mHealth app companies have fewer than 10,000 monthly active users, a standard industry engagement metric [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 90% of all mHealth apps are uninstalled within 30 days, and 83% of mHealth app companies have fewer than 10,000 monthly active users, a standard industry engagement metric [ 14 ]. Systematic reviews of controlled studies on this topic suggest that tailoring content to individual characteristics, regularly updating apps, and incorporating a range of behavior change techniques, for example, may boost engagement [ 10 - 13 ]. To date, however, evaluations of only a few mHealth apps out of the thousands in the app stores have been published in peer-reviewed scientific journals [ 12 ].…”
Section: Introductionmentioning
confidence: 99%